Effects of focused direct and metalinguistic corrective feedback on L2 learners’ writing / Gringo Magbanua Jusa - Gringo Magbanua, Jusa (2017)
Three intact groups (CG group, DCF group, and MCF group) were placed into treatment procedures to compare direct (DCF) and metalinguistic corrective feedback (MCF) and its effects on knowledge acquisition in basic tenses in writing. Three tests given in three-testing time were employed to measure the CF efficacy and its effects on the learners’ implicit and explicit knowledge. Picture Narrative Writing Test was used to measure the efficacy of corrective feedback in writing, while Metalinguistic Knowledge Test and Timed Grammatical Judgment Test were used to measure explicit and implicit knowledge respectively. Through mixed-method design, SPSS (two-way mixed ANOVA) was used to analyse the efficacy of CF, while thematic analysis was used for the qualitative interview data. Quantitative findings revealed that MCF is more effective than DCF in improving the writing accuracy of the students. This result was further extended to the improvement of implicit and explicit knowledge of basic English tenses. On the other hand, the control group did not show any progression in any of the three tests. The qualitative thematic analysis also revealed the benefits of employing MCF as a corrective feedback which further validated the statistical result. Specifically, most of the learners in the MCF group claimed that the operationalized feedback encouraged critical thinking. Through these findings, the study has provided pedagogical implications and future research recommendations which could further enhance the study and validate the existing claims in this area.